Характеристики крупности дисперсных алмазосодержащих материалов - Олейник, Н.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
Results of the description of character of distribution of particles of a disperse product of synthesis of diamond after various kinds of processing, raw materials, powders in the form of total characteristics of the sizes approximated by eksponentsialno-sedate dependence Rozina-Rammlera are presented.